Performance evaluation of routing protocols in vehicular ad hoc networks. (1st January 2011) - Husain, Akhtar; Kumar, Brajesh; Doegar, Amit
Vehicular ad hoc network (VANET) is an emerging new class of mobile ad hoc networks, which can be used to improve road safety and comfort of the passengers inside vehicles. Due to mobility constraints and high dynamics, routing is a more challenging task in VANETs. In this work, we evaluate the performance of the conventional ad hoc routing protocols in vehicular network environment. The objective of this study is to assess the applicability of these protocols in different vehicular scenarios. Two location-based and two topology-based ad hoc routing protocols are evaluated in city and highway scenarios. Mobility model has significant effects on the simulation results. Conventional mobility models are unsuitable for VANET simulations. We used intelligent driver model based tool VanetMobiSim to generate realistic mobility traces. Performance metrics such as packet delivery ratio, normalised routing load, end-to-end delay, and throughput are evaluated using NS2.